DIPLOMASI INDONESIA : pada Peningkatan Pengiriman Tenaga Perawat Dalam Kerangka Indonesia-Japan Economic Partnership Agreement (IJEPA) Tahun 2010-2018 - GITA SUCI HAYUNINGTYAS, (2020)
This research aimed to identify and analize act of diplomacy that undertaken by Government of Indonesia to increase the number of Indonesian nurses to work in Japan under the framework of bilateral cooperation Indonesia-Japan Economic Partnership Agreement (IJEPA). Japan is the country with the largest elderly population in the world, that condition leads to a labor deficit. This made Japan accept Indonesia's proposal on sending Indonesian nurses to work in Japan's hospitals. The cooperation has been running for ten years from 2008 until 2018. This research focused on the 2010-2018 period, since at that period, there was a declining number of nurses sent to Japan. This research used theory of diplomacy and concept of Economic Partnership Agreement (EPA). This research used descriptive methods with qualitative research approach to collect data of diplomacy. The result exhibited that diplomatic efforts by Government of Indonesia have not been able to increase the numbers of Indoensian nuses sent to Japan. The numbers of foreign nurses working in Japan was limited by the quota given by Government of Japan. Key words: Diplomacy, Nurses, Indonesia-Japan Economic Partnership Agreement (IJEPA)